Mineral element discrimination of Selenium-enriched rice in Ningxia and its quality evaluation - YANG Xiao-chen (Shipin yu jixie, 2022)
Objective: The element content and physical and chemical quality were analyzed from the nutritional quality of Selenium (Se)-enriched rice in Ningxia. Methods: 25 rice samples from different brands in Ningxia were selected as the research object, and 26 mineral elements in which were determined by inductively coupled plasma mass spectrometry (ICP-MS), and multivariate statistical analysis of these elements was conducted. Results: Through the analysis of the difference of element content between Se-enriched rice and ordinary rice, the quality of Se-enriched rice was distinguished. Moreover, it was found that Se-enriched rice was rich in four kinds of elements such as Ca, Sn, K and Mg. Other quality indexes of Se-enriched rice were analyzed. It was found that Se-enriched rice was imperfect, with low grain, low yellow grain, low chalkiness, high head rice rate, high amylose, high taste value, high freshness score, suitable hardness, elasticity and adhesion, good palatability, and high appearance quality and edible quality. Conclusion: Se-enriched rice can be distinguished by the difference of element content, and the Se-enriched rice in Ningxia has high nutritional value and eating quality.